Bi-lateralized Whorfian effect in color perception: Evidence from Chinese Sign Language. (February 2019) - Xia, Tiansheng; Xu, Guiping; Mo, Lei
Abstract: Converging behavioral and neural studies have shown a right visual field (RVF) advantage on language's effect on color categorical perception (the Whorfian effect). But little is known about the effect of sign language on deaf people's perception of color categories. To examine whether this lateralized effect also occurs in sign language systems, both behavioral and electrophysiological studies were conducted using visual search and oddball tasks respectively. The visual search results revealed that reaction times to targets were faster when the target and the paired distractor colors were easy to sign than when they were hard to sign, both in RVF and left visual field (LVF), and further, the LVF Whorfian effect was disrupted when participants performed the spatial interference secondary task. In the oddball task, the amplitude of the vMMN component evoked by the within-category deviant was significantly smaller than that evoked by the between-category deviant when displayed in either the RVF or the LVF. Both the behavioral and electrophysiological findings show that the language of the deaf affects their color perception bi-laterally, which suggests that the nature of language decides the pattern of the Whorfian effect. Highlights: The right visual field (RVF) advantage exists on color categorical perception. Whorfian effect exhibits in the RVF and left visual field (LVF) in sign languages. The LVF Whorfian effect of deaf signers was disrupted when performing spatial task. The vMMN evoked by color categorical perception displayed in either RVF or LVF. Bi-lateral Whorfian effect may be because sign language needing spatial processing.